Beyond information sharing: stimulating youth recovery and resilience post-disaster through social media. (18th August 2021) - Berard, Ashley A.; Plush, Tamara; Cox, Robin S.; Hill, Tiffany T.
In disaster response, social media can perform a critical role in disseminating evacuation information, connecting friends and family, and linking those affected to urgently needed services. Less explored is the role social media might play after disaster in online and offline processes of recovery and resilience - especially for young people deeply engaged in its use. This paper considers the possibilities through the #YouthVoicesWB campaign, which was developed with youth a year after the Canadian 2016 Horse River wildfire disaster (a.k.a., the Fort McMurray wildfire). It offers insight into the campaign - an emergent approach to recovery that created agentic spaces for youth through online and offline interactions. It also examines the value of youth-adult partnerships when building a social media platform aimed at strengthening the voices of youth post-disaster. Ultimately #YouthVoicesWB demonstrates the value of listening to youth; and shows how including youth in recovery decision-making as key stakeholders holds potential for more resilient communities.